Sample learning modules in communication arts for grade six learners of elementary science - De la Peña, Betty A. 1949- (1977)
These sample Learning Modules in Communication Arts for Grade Six Learners of Elementary Science are intended as self-instructional materials. Materials are based on rhetorical facts rather than on the linguistic elements and vocabulary items. The materials integrated the four language skills: listening, speaking, reading, and writing. Statistical data based on the results of the pre- and post- tests showed that there was positive learning due to the use of the modularized materials.
"May, 1977."
Vita.
Thesis (M.Education : English as a Second Language)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Elementary) -- Philippines; Language arts (Elementary) -- Philippines; Teaching -- Philppines -- Aids and devices